Results of the sensory analysis of precision maize production - Duzs, László; Ragán, Péter; Rátonyi, Tamás (Acta Agraria Debreceniensis, 2019)
This research was carried out in 2018, at the Látókép Experimental Station of the University of Debrecen in a moderately warm and dry production area, on deep humus layered medium-hard calcareous chernozem soil. In the scope of the research, the chlorophyll content of maize (Zea mays L.) was examined under field circumstances by means of local sensory measurements and we were looking for correlation between the obtained values and the amount of yield. Our measurements were carried out with Minolta SPAD-502 and GreenSeeker devices at 3 measurement times (4 leaf stage, 10 leaf stage and silking). It was found that phenological phases had an effect on the obtained SPAD and NDVI values and were in a slightly significant correlation with the yield. The most significant correlation was found between the results obtained during silking and the amount of yield. This may be because the least time has passed between the measurement time and harvest. Results obtained during the 10-leaf stage show excessive values in each case, which can be due to a measurement error. It was found that the phenological phase had an effect on the correlation of SPAD and NDVI values and the amount of yield. As the phenological phase progressed, the correlation between the measured results and yield has increased.